Socio-Cultural and Economic Causes of Corruption and Challenges in Its Control in Nepal - Raut, Sunita; Rawat, Chameli (Bagiswori Journal, 2025)
This study is based on descriptive research methodology and employed structured questionnaire tools to obtained data and information. A survey sample was confirmed through purposive sampling and sample unit was 100 respondents. Who were officers and staff currently working in the offices of the CIAA, NVC, CIB, and DAO, all of them were primarily responsible for investigative research and action to combat with corruption in Nepal. The quantitative data were analyzed using simple statistical tools and MS excel particularly. Qualitative data were analyzed constructing theme and using Word Cloud to visualize subjective information. Based on the objective, data revealed that corruption is significantly increasing in current time though Nepal government structured so many mechanisms to control corruption. Similarly, the most common forms of corruption identified were bribery, embezzlement, and nepotism correspondingly. The most common cause of corruption is political in Nepal. In the same way significant number of respondents opined that Money is everything type of believe system, erosion on moral ethics and values and no social boycott of corrupt people are three socio-economic cause of corruption. Likewise Political interference, Lack of enforcement, institutional corruption are the big challenges to control corruption in Nepal. The study highlights strategic focus on to control political corruption; strengthen public policy and anti-corruption strategies to foster the transparency. This study also paved the way to the research hers to conduct further study relating to anti-corruption and good governance initiatives in Nepal.